2015
DOI: 10.1530/erp-14-0070
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional global and segmental longitudinal strain: are the results from software in different high-end ultrasound systems comparable?

Abstract: To compare the peak global longitudinal myocardial strain (PGLS) and peak segmental longitudinal myocardial strain (PSLS) values by speckle-tracking echocardiography (STE) obtained using two different echocardiography devices. STE is an emerging quantitative ultrasound technique that allows an accurate evaluation of global and segmental myocardial function. However, there is a lack of standardization of the acquired data among different manufacturers. Sixty-three subjects, mean age 56.2±10.4 years, underwent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The cutoff value of -18 seemed appropriate because it was derived from previous studies involving healthy children who represented the age groups of the patients included in our study. [19][20][21][22] Finally, it was not possible to make multiple comparisons between variables such as age, duration of disease, gait loss, use of corticosteroids, and affected exons, because the sample size was small and the frequency of some variables was very low in the groups compared. We found that half of DMD patients could benefit from the echocardiographic myocardial strain analysis for the detection of early LVSD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cutoff value of -18 seemed appropriate because it was derived from previous studies involving healthy children who represented the age groups of the patients included in our study. [19][20][21][22] Finally, it was not possible to make multiple comparisons between variables such as age, duration of disease, gait loss, use of corticosteroids, and affected exons, because the sample size was small and the frequency of some variables was very low in the groups compared. We found that half of DMD patients could benefit from the echocardiographic myocardial strain analysis for the detection of early LVSD.…”
Section: Discussionmentioning
confidence: 99%
“…LVEF was considered normal if ≥52%, as defined in recent guidelines for male patients . GLS was considered normal if it was ≤–18% . The DMD patients with normal LVEF (≥52%) were classified, based on TTE features, into the normal LVSF group (GLS ≤ –18%) and the early LVSD group (GLS > –18%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All measurements followed the American Society of Echocardiography guidelines (21). In addition, the global longitudinal strain was assessed off-line using the EchoPac 7 software (automated function imaging, AFI) (22). Global strain is a novel indicator of the overall systolic function of left ventricle, and may reveal heart disease already in early stage, when EF is still normal (23).…”
Section: Echocardiographymentioning
confidence: 99%
“…The bull’s eye plots displayed in this review are generated using EchoPAC software by GE Vivid E9. Previous studies showed that the values of global longitudinal systolic strain obtained with Philips and GE echo systems have good correlations either in healthy population or patients [ 9 11 ]. The better agreement is observed in cardiac patients than in healthy controls [ 11 ].…”
Section: Reviewmentioning
confidence: 99%